A SNP Resource for Human Chromosome 22: Extracting Dense Clusters of SNPs From the Genomic Sequence - Dawson, Elisabeth; Chen, Yuan; Hunt, Sarah; Smink, Luc J.; Hunt, Adrienne; Rice, Kate; Livingston, Simon; Bumpstead, Suzannah; Bruskiewich, Richard; Sham, Pak; Ganske, Rocky; Adams, Mark; et al. (Genome Research, 2001)
The recent publication of the complete sequence of human chromosome 22 provides a platform from which to investigate genomic sequence variation. We report the identification and characterization of 12,267 potential variants (SNPs and other small insertions/deletions) of human chromosome 22, discovered in the overlaps of 460 clones used for the chromosome sequencing. We found, on average, 1 potential variant every 1.07 kb and approximately 18% of the potential variants involve insertions/deletions. The SNPs have been positioned both relative to each other, and to genes, predicted genes, repeat sequences, other genetic markers, and the 2730 SNPs previously identified on the chromosome. A subset of the SNPs were verified experimentally using either PCR–RFLP or genomic Invader assays. These experiments confirmed 92% of the potential variants in a panel of 92 individuals. [Details of the SNPs and RFLP assays can be found at http://www.sanger.ac.uk and in dbSNP.]